Pelatihan Kepemimpinan, Investasi Keuangan dan Dasar Akuntansi Serta Peningkatan Kompetensi, Motivasi dan Kedisiplinan yang Bertujuan untuk Mensosialisasikan Kewajiban Belajar 12 Tahun dan Mengedukasi Mengenai Perlindungan Guru dalam Kegiatan Belajar Pada Siswa-Siswi Yayaysan Mutakabbir Kabupaten Bogor - Muhammad Rizal Saragih; Rusdi Rusdi; Dinar Ambarita; Prima Sadewa; Mawardi Nurullah; Julian Muhammad Hasan; Liana Dwi Septiningrum; Eka Rima Prasetya; Moh. Yuddy Yudawirawan; Dewi Ulfah Arini; Sujarwo Sujarwo; Muslim Muslim; Fery Citra Febriyanto; Eko Sasongko Priyadi; Diantia Amendy; Indra Wadi; Mhd. Ali Akbar; Sri Indarti (Jurnal PKM Manajemen Bisnis, 2026)
This community service program (PKM) was conducted to address the need for improving students’ and teachers’ understanding of leadership, financial literacy, and basic accounting, while also strengthening competence, motivation, and discipline. Additionally, the program aimed to socialize the importance of the 12-year compulsory education policy and to educate participants about teacher protection in the learning process. The objective of this activity was to enhance knowledge, awareness, and practical skills among students and teachers at Yayasan Mutakabbir, Bogor. The PKM was carried out on April 12, 2026, at Yayasan Mutakabbir Kemang, Bogor. The implementing team consisted of 12 lecturers from Universitas Pamulang, with 23 participants including students and teachers. The methods used in this activity included material presentations, practical exercises, discussions, and question-and-answer sessions. The implementation stages consisted of preparation, execution, and reporting. The results showed increased participant understanding of leadership principles, financial investment basics, and accounting concepts. Participants also demonstrated improved motivation, discipline, and awareness of the importance of continuing education and teacher protection. The interactive approach contributed to active engagement and positive feedback from participants.